Model-free method for isothermal and non-isothermal decomposition kinetics analysis of PET sample - Saha, B.; Maiti, A.K.; Ghoshal, A.K. (Thermochimica acta, 2006)
Pyrolysis, one possible alternative to recover valuable products from waste plastics, has recently been the subject of renewed interest. In the present study, the isoconversion methods, i.e., Vyazovkin model-free approach is applied to study non-isothermal decomposition kinetics of waste PET samples using various temperature integral approximations such as Coats and Redfern, Gorbachev, and Agrawal and Sivasubramanian approximation and direct integration (recursive adaptive Simpson quadrature scheme) to analyze the decomposition kinetics. The results show that activation energy ( E α ) is a weak but increasing function of conversion ( α) in case of non-isothermal decomposition and strong and decreasing function of conversion in case of isothermal decomposition. This indicates possible existence of nucleation, nuclei growth and gas diffusion mechanism during non-isothermal pyrolysis and nucleation and gas diffusion mechanism during isothermal pyrolysis. Optimum E α dependencies on α obtained for non-isothermal data showed similar nature for all the types of temperature integral approximations.